DECISION-MAKING STRATEGIES REGARDING LOGISTICS ORGANIZATION - Olariu, Ioana (Studies and Scientific Researches. Economics Edition, 2014)
In the face of higher costs of operation and increasing pressures from customers for better service, the logistics organization must adapt to meet the challenge. An understanding of the factors that make organizations effective, and a knowledge of how these factors interrelate, are the first steps towards developing the system for a firm’s customers. Logistics organizations must of necessity become more cost and service efficient. An understanding of the factors that affect a firm’s organizational effectiveness, along with strategies to reveal weaknesses or deficiencies, can help create more efficient logistics systems. Organizational changes form the basis for procedural modifications that can reduce costs or improve service. Many firms have shown significant improvements in their logistics cost-service mix as a result of organizational changes. Logistics organizations are generally structured along the following lines: strategic versus operational, centralized versus decentralized and line versus staff, in various combinations. There is no single ideal organizational structure, but there are important elements that comprise an effective organization. In general, the factors contributing to organizational effectiveness can be categorized as organizational characteristics, environmental characteristics, employee characteristics, and managerial policies and practices.